2006
DOI: 10.1159/000097056
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Recanalization of Occluded Standard Extracranial-Intracranial Arterial Bypass

Abstract: Background: In the event of early failure of standard extracranial-intracranial arterial bypass, elective but prompt revision surgery is generally attempted under the assumption that early occlusion is permanent. However, little is known about the occurrence of spontaneous revascularization. Objective: To estimate the frequency and time course of spontaneous recanalization in primary extracranial-intracranial arterial bypass occlusion and re-evaluate diagnostic and therapeutic options facing spontaneous develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Bypass patency is an important determinant factor to evaluate the success of the surgery and the long-term outcome of the patient (8, 11, 20). Although the primary bypass function has been evaluated during surgery, there is a 4–10% chance of early bypass failure (21). Yoon et al analyzed the long-term patency of 430 bypasses with postoperative imaging and found out that the overall patency rate of bypasses in MMD was 98% (8).…”
Section: Discussionmentioning
confidence: 99%
“…Bypass patency is an important determinant factor to evaluate the success of the surgery and the long-term outcome of the patient (8, 11, 20). Although the primary bypass function has been evaluated during surgery, there is a 4–10% chance of early bypass failure (21). Yoon et al analyzed the long-term patency of 430 bypasses with postoperative imaging and found out that the overall patency rate of bypasses in MMD was 98% (8).…”
Section: Discussionmentioning
confidence: 99%
“…This high recanalization rate rarely occurs after STA-MCA bypass for obstructive cerebrovascular diseases other than MMD, and the disease-specific nature of MMD is considered. [ 27 ] The first is the high degree of angiogenesis in patients with MMD. [ 6 , 16 ] Even in STA grafts where luminal blood flow is disrupted, blood flow may enter the surrounding connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have proposed that the incidence of perioperative anastomotic occlusion in MMD patients undergoing direct bypass procedures, ranged from 4.0% to 35.5% [ 21 , 22 , 23 ]. Spontaneous recanalization of the occluded anastomosis may occur in many occluded patients (30.4–100.0%) during 3–12 months of postoperative CTA follow-up [ 21 , 22 ]. In this study, perioperative anastomotic occlusion occurred in eight hemispheres, with a perioperative graft patency rate of 91.5%.…”
Section: Discussionmentioning
confidence: 99%